(سورية والعراق) و استراتيجية الولايات المتحدة في الشرق الأوسط - حيدر عفيف; اسماعيل عصام; ميليش فريد (مجلة جامعة تشرين للبحوث والدراسات العلمية- سلسلة العلوم الاقتصادية والقانونية, 2018)
بعد أن كانت الطبيعة الثنائية لقيادة النظام الدولي تضع سقفاً محدداً لتدخل القطبين في الشؤون الإقليمية لمناطق معينة, وقد وفرّت حرب الخليج الثانية في 15 كانون الثاني 1991م، المناخ الملائم لتدعيم الوجود والنفوذ الأمريكي في المنطقة، وخصوصاً التواجد العسكري, فكانت هذه الحرب أهم دليل على مدى النفوذ الذي أصبحت الولايات المتحدة تتمتع به في إدارة النزاعات الإقليمية من ناحية، وعلى الواقع الذي باتت بعض الدول في منطقتنا تواجهه وخاصة سورية والعراق في غياب قطب دولي موازن للقطب الأمريكي, بعد الأنعكاسات المباشرة على البيئة الشرق أوسطية، ذلك أنّ مسرح العمليات العسكرية الأمريكية انطلق من هذه المنطقة بدءاً بالحرب على أفغانستان ثمّ العراق، ثم ما نراه اليوم من استهداف لسورية وفق مزاعم الربيع العربي, والتي باتت وفقه الإدارة الأمريكية مقتنعة بضرورة تغيير خريطة الشرق الأوسط السياسية على مستويات عديدة. After the bilateral nature of the leadership of the international system to place caps checked for the intervention of the poles in regional affairs to certain areas, and the second Gulf War and fled in the January 15, 1991 m, suitable climate to strengthen the presence of US influence in the region, especially the military presence, this war was the most important evidence of the extent of the influence that became the United States enjoyed in regional conflict management on the one hand, and on the fact that now some countries in our region faces in the absence of an international pole counterweight to the American tycoon, is reflected directly on the Middle Eastern environment, because the US military theater of operations launched from this area starting with the war in Afghanistan and then Iraq, then what we see today from targeting Syria according to the Arab spring allegations, and the US administration is now convinced of the need to change the political map of the Middle East on many levels.